Financial Management Training for MSMEs to Increase Business Efficiency and Profitability UKM Sinarmukti Kebon Kalapa RT 02 RW 02 Margamukti Village, North Sumedang District, Sumedang Regency (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The significance of financial management training for Micro, Small, and Medium Enterprises (MSMEs) lies in its pivotal role in the progression of the MSME sector, which forms the backbone of the economy in numerous countries. The objective of this training is to impart knowledge and financial management skills to MSME owners, enabling them to enhance the efficiency and profitability of their businesses. This program encourages business owners to enhance the efficiency and profitability of their enterprises. By means of training materials encompassing financial planning, financial record-keeping, cash management, and financial report analysis, MSMEs in Margamukti Village can bolster their capabilities in effectively managing the financial aspects of their businesses. The significance of this training cannot be overstated. MSME owners with a solid grasp of financial management can make more informed decisions, mitigate unforeseen financial challenges, and strategize for sustainable business expansion. Furthermore, they are better positioned to secure external financing and attract potential investors who can contribute to the development of their businesses. Interactive and practical training methods, including courses, case studies, and simulations, facilitate MSME owners in comprehending and implementing financial management principles within the framework of their businesses. By doing so, they can mitigate financial risks, optimize the utilization of capital, and strategize for sustainable business expansion. This program represents a constructive measure in bolstering the growth of MSMEs, reinforcing the village economy, and forging fresh prospects for the triumph of MSME owners in their enterprises. The collaborators in this community service initiative are UKM Sinarmukti, situated in Kebon Kalapa Hamlet, RT 02 RW 02, Margamukti Village, North Sumedang District, Sumedang Regency.